KINERJA WIRAUSAHA DAN ORIENTASI KEWIRAUSAHAAN PELAKU UMKM OLAHAN ABON IKAN - Wulandary, Ayu; Burhanuddin, Burhanuddin; Priatna, Wahyu Budi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
Indonesia is a country that has a long coastline and the development of fisheries and marine sector. Utilization of marine resources is accompanied by the use of capture fisheries to produce processed products. One of processed fishery product is fish shredded with the central area of Makassar City. Production inputs that have fluctuating prices are the primary cause of business performance disruption. The study was conducted in Makassar with 40 respondents of UMKM. Data analysis performed is to analyze the relationship between business performance with entrepreneurship orientation using Spearman analysis. The findings indicate that the majority of entrepreneurial orientations are significantly related to business performance. Keinovativan is related to the overall variable of business performance, proactive and dares to take risks related to company growth and Customer Satisfaction. Aggressiveness is related to company growth and competitive advantage. While the autonomy is not related to business performance